Exit west - Hamid, Mohsin, 1971- (Gurgaon Penguin, 2017)
In a country teetering on the brink of civil war, two young people meet--sensual, fiercely independent Nadia and gentle, restrained Saeed. They embark on a furtive love affair, thrust into premature intimacy by the unrest roiling their city. When it explodes, turning familiar streets into a patchwork of checkpoints and bomb blasts, they begin to hear whispers about doors--doors that can whisk people far away, if perilously and for a price. As violence and the threat of violence escalate, Nadia and Saeed decide that they no longer have a choice. Leaving their homeland and their old lives behind, they find a door and step through.
Published in the US by Riverhead Books, 2017.
Keywords: Choice (Psychology) -- Fiction; Refugees -- Fiction; Man-woman relationships -- Fiction